Report of the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) 2015 - United Nations Scientific Committee on the Effects of Atomic Radiation (United Nations, 2016)
Since the establishment of the United Nations Scientific Committee on the Effects of Atomic Radiation by General Assembly resolution 913 (X) of 3 December 1955, the mandate of the Committee has been to undertake broad assessments of the sources of ionizing radiation and its effects on human health and the environment. In pursuit of this mandate, this report presents the deliberations of the Committee at its Sixty-second session (1-5 June 2015).